SOSIALISASI MENINGKATKAN PENCEGAHAN DAN RESPON CEPAT TERJADINYA KEKERASAN TERHADAP ANAK DI TINGKAT DESA SAMPIR - Iron Fajrul Aslami; Yudi Prasetiya; Nindi Khoirunisa; Sofah Sofah (LPPM Universitas Bina Bangsa, 2022)
Sampir Village is a village located in Waringin Kurung sub-district, Serang Regency. Sampir Village has an area of 269.5 hectares with longitude coordinates 106.05031 and latitude coordinates -6.101572 with an altitude of 1200 MDPL with the number of RT: 10 and RW 3. The environmental community of Sampir Village is still not yet aware of the dangers of violence against children and the rapid response to violence against children at the village level. The purpose of this socialization is to find out what forms of violence against children are and how to protect children as victims of crime according to Indonesian criminal law. The forms of violence that occur against children are physical violence, psychological/emotional violence and sexual violence, including: being pinched, pushed, bitten, strangled, kicked, splashed, slapped, told to push up, told to run, threatened, scolded, being scolded, spat on, shaved, expelled, forced to clean toilets, forced to pull grass, seduced, poked, forced to masturbate, oral sex, raped and so on. As already provided by Law No. 23 of 2002 on Child Protection, which was amended by Law No. 35 of 2014, Law Number 15 of 2003 concerning Criminal Acts of Terrorism, Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims